Comparison of ultimate bearing capacity obtained by pile driving analyzer and maintained load test - Rajasvaran, Kamalendran N. (2007)
In Malaysia, Maintained Load Test (MLT) is the most common static load test used for testing of driven reinforced concrete (RC) piles, while Pile Driving Analyzer (PDA) is currently the most popular dynamic test method. MLT provides relatively accurate information on ultimate pile capacity and settlement but is costly, time consuming and difficult to carry out. PDA is much more timesaving, less expensive and can be carried out with relative ease, but the results are subject to uncertainties and interpretations of wave stress propagation theories. Results of pile load tests at a hypermarket development were studied and analysed to create a comparison between MLT and PDA. From the study, ultimate pile capacities derived from analysis of PDA were consistently higher than results from MLT. Comparison of pile settlement results for MLT and PDA was observed to be inconsistent. The study also recognises that Davisson’s Method is used to obtain ultimate pile capacity from MLT as it is more conservative compared with other calculation methods. PDA results were observed to be satisfactory in determining ultimate pile capacity, but a coefficient of 0.9 or a 10% reduction is suggested to be applied to values derived from PDA. For future pile testing programs, there is a potential for an increase of PDA tests to be carried out. However, a limited number of MLT must also be carried out to determine accuracy of parameters and soil models used in PDA tests.